Position Tracking Control of an Electro-Hydraulic Servo System Based on Nonlinear Disturbance Observers - Qingqing Xu; Yaxing Lu; Mingxing Yang; Xing Zhang (IEEE Access, 2024)
In order to ensure a precisely controlled electro hydraulic servo system, a sliding mode control algorithm based on nonlinear disturbance observers (NDOB-SMC) is developed in this study. Firstly, the basic principles of hydraulic actuators and electro-hydraulic position servo control mathematics are studied, and theoretical models are utilized to derive the state equations of the controlled system. Furthermore, considering that the sliding mode control is invariant to external disturbances and parameter changes, it is designed to be resilient against the unreliable hydraulic position servo system. In the meanwhile, nonlinear disturbance observers are added to the system to offset its output and enhance tracking capabilities even more. The Lyapunov theory is used to demonstrate the stability of the control strategy. Finally, the efficacy and dynamic performance of the NDOB-SMC method are preliminary confirmed using the co-simulation platform of AMESim and Matlab/Simulink. The numerical simulation results show that the suggested approach offers greater control accuracy and improved robustness for hydraulic position servo systems when compared to the conventional PI and sliding mode control methods.